A Probe into the Extraversion and L2 Pronunciation Relationship - Kralova, Zdena (Communications - Scientific letters of the University of Zilina, 2012)
The study assessed the relation between the overall degree of the perceived foreign accent in non-natives’ English speech and some personal variables which include global factors (extraversion, anxiety, tough-mindedness, independence, self-control) and contributing primary factors, extraversion being the focus of our attention. Five native speakers of English were asked to auditorily evaluate the samples of free English speech produced by each of 75 non-native speakers using the equal-appearing interval 5-point scale. The 10-point scale was used to rate each of the personality variables for non-native speakers and the interclass correlation coefficients were calculated to identify the relevant predictors of L2 pronunciation quality.